Energy barriers at the ends of carbon nanotube bundles: Effects on interstitial adsorption kinetics - Calbi, M. Mercedes (2005)
We investigate the presence of adsorption sites and energy barriers near the ends of carbon nanotube bundles to determine their consequences on gas adsorption in the interstitial channels between the tubes. In the case of H2 molecules adsorbing in bundles of closed (10,10) tubes, a high binding energy site followed by a potential barrier lie right before the entrance to the interstitial channels, producing a dramatic slowing down of interstitial adsorption kinetics.